Faktor-Faktor Yang Mempengaruhi Pendapatan UMKM (Studi Kasus Kecamatan Polewali Kabupaten Polewali Mandar) - Nugraha A, Arif; Hastuti, Diah Retno Dwi; Alam, Syamsu (Jurnal EMT KITA, 2025)
The economic crisis that hit the world automatically worsened the economic situation in Indonesia in the period from 1997 to 1998. During the crisis, only the Micro, Small and Medium Enterprises (MSMEs) sector was able to survive strongly. This phenomenon shows that MSMEs can be productive activities that support economic growth both macro and micro in Indonesia, and have a positive impact on the development of other sectors. Law Number 20 of 2008 concerning Micro, Small, and Medium Enterprises (MSMEs) stipulates regulations for the MSME sector. Micro, Small and Medium Enterprises (MSMEs) are the top priority in national development and the presence of digital technology in the era of the industrial revolution 4.0 is a very important factor for the development of business lines for industry players or businesses. This study aims to determine the influence of business duration and promotion methods on MSME income in Polewali District, Polewali Mandar Regency. The methodology used in this study is a quantitative approach where the source of data is obtained directly (primary) through the discourse method and the distribution of questionnaires. The results of this study are that the variables of business duration and promotion simultaneously have a significant influence on MSME income. Meanwhile, partially the business duration variable does not have an effect on MSME income, on the contrary, the Promotion variable has a significant influence on MSME income. The value of the determination coefficient is 90%. This shows that the variables of business duration and promotion variables greatly affect the change in MSME income in Polewali District, Polewali Mandar Regency.